1995
DOI: 10.1177/0022022195263003
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Managerial Values in The People'S Republic of China and Hong Kong

Abstract: The four managerial values of power distance, uncertainty avoidance, masculinity, and individualism measured by self-reports from 350 managerial trainees in the People's Republic of China (PRC) and Hong Kong provided the database for this research. The results indicate support for the convergence theory proposition that managerial values converge with increased industrialism. Further analysis revealed that it was the younger PRC managerial trainees who had values that were closest to those of Hong Kong manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Although fairness expectation may be considered a universal value, there are several studies (i.e., Birnbaum-More & Wong, 1995;Itoi, Ohbuchi, & Fukuno, 1996;Leung, 1987;Leung, Bond, Carment, Krishnan, & Liebrand, 1990, Leung & Lind,1986Steiner & Gilliland, 1996;Tata, 2005) which show that people may perceive the fairness level of practices differently and that they may react to unfairness differently in different countries, due to the influence of their cultures. Muslim students are one of the groups who have complained of being targeted for Islamophobia, discrimination, and unfairness.…”
Section: Introductionmentioning
confidence: 99%
“…Although fairness expectation may be considered a universal value, there are several studies (i.e., Birnbaum-More & Wong, 1995;Itoi, Ohbuchi, & Fukuno, 1996;Leung, 1987;Leung, Bond, Carment, Krishnan, & Liebrand, 1990, Leung & Lind,1986Steiner & Gilliland, 1996;Tata, 2005) which show that people may perceive the fairness level of practices differently and that they may react to unfairness differently in different countries, due to the influence of their cultures. Muslim students are one of the groups who have complained of being targeted for Islamophobia, discrimination, and unfairness.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, research has demonstrated regional differences in the Chinese culture (e.g., Birnbaum-More, Wong, & Olve, 1995). Assuming that national culture influences individual and organizational behaviors in a society, we predict that the regional differences in Chinese culture should also influence LMX in Chinese societies.…”
Section: Literature Reviewmentioning
confidence: 80%
“…Previous studies have shown that five cultural dimensions (Hofstede, 2001) significantly affect management values. Cultural dimensions of individualism, uncertainty avoidance, masculinity, power distance and long-term orientation were shown to have a significant relationship with managerial values and decisionmaking (Birnbaum-More, Wong and Olve, 1995;Hofstede, 2001;Robertson, 2000 andWestwood andPosner, 1997).…”
Section: Independent Variable Dependent Variablementioning
confidence: 99%